The Role of Structure-Seeking in Moral Punishment. - Stanley, Matthew L.; Huang, Shenyang; Marsh, Elizabeth J.; Kay, Aaron C. (Social Justice Research, 2023)
Four studies (total N = 1586) test the notion that people are motivated to punish moral rule violators because punishment offers a way to obtain structure and order in the world. First, in a correlational study, increased need for structure was associated with the stronger endorsement punishment for moral rule violators. This relationship between need for structure and punishment was not driven by political conservatism. Three experimental studies then tested, and corroborated, our main causal hypotheses: that threats to structure increase punitive judgments for moral rule violators (i.e., a compensatory mechanism; Study 2) and that a lack of punishment for wrongdoing (relative to punishment for wrongdoing) makes the world seem less structured in the moment (Studies 3 and 4). We compare and contrast our structure-based account of moral punishment to other theories and findings across the punishment literature.